Ketepatan Pengaruh Manajemen Logistik Terhadap Tingkat Kepuasan Pelanggan PT. Bhinneka Bajanas Cabang Cikarang - Yosephyn Patria Larici; Fino Wahyudi Abdul (Institut Ilmu Sosial dan Manajemen Stiami, 2019)
This study aims to determine how much influence logistics management has on the level of customer satisfaction at PT. Bhinneka Bajanas Cabang Cikarang. The population of this research is PT. Bhinneka Bajanas Cabang Cikarang customers as many as 100 people, while the sample in this study were 50 people using the Accident Sampling method, then the data was obtained by simple linear regression analysis. The independent variable in this study is logistical management and the dependent variable is customer’s satisfaction. The results of this study indicate that logistics management has an influence on customer satisfaction. It can be seen from the results of T test, the analysis’ results show the value of T count> T table (6.327> 2.01). It means that H0 is rejected and H1 is accepted, or there is an effect (partially) between Logistics Management and Customer Satisfaction Levels.